ASPEK HUKUM PEMBUKTIAN DAN PERLINDUNGAN HAK DALAM ADMINISTRASI PUBLIK: ANALISIS YURIDIS TERHADAP PROSES ADMINISTRASI DAN SENGKETA TATA USAHA NEGARA - Gunawan Widjaja (ADMIN: Jurnal Administrasi Negara, 2026)
Public administration in Indonesia faces a crucial challenge in maintaining a balance between the authority of civil servants and the protection of citizens’ rights through fair evidentiary mechanisms and effective dispute resolution, as stipulated in Law No. 5 of 1986 on Administrative Courts and Law No. 30 of 2014 on Government Administration. This article analyses the legal aspects of evidence under the principle of the reversed burden of proof, which requires civil servants to prove the validity of administrative acts through at least two valid forms of evidence (documents, witnesses, experts, admissions, and judicial knowledge), as well as the hierarchy of rights protection through preventive administrative measures, Ombudsman oversight, and remedial actions in the Administrative Court (PTUN) that guarantee the annulment of illegal decisions along with compensation for material and non-material damages. A normative legal approach using a statute approach and analysis of court rulings reveals key challenges such as unequal access to information, weak enforcement of rulings, and regulatory fragmentation that hinder good governance; consequently, recommendations include amending the Administrative Court Law to mandate digital evidence, strengthening enforcement sanctions, and digitising administrative processes to realise the rule of law and human rights-oriented bureaucratic accountability.